2010
DOI: 10.3928/08910162-20100616-02
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in the Workplace—A Qualitative Study of Newly Licensed Registered Nurses

Abstract: Bullying in the workplace is associated with negative job satisfaction and retention. It has also been found to have adverse effects on the health of employees. Using a qualitative descriptive design, this study examined the stories of bullying among nurses based on actual or witnessed experiences. One hundred eighty-four newly licensed U.S. nurses responded to an open-ended question on a survey about bullying mailed to their homes. Four major themes emerged that related to varying types of bullying behaviors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 29 publications
2
58
0
4
Order By: Relevance
“…Bullying in the workplace runs counter to the espoused ethical values of health care organizations and must be challenged by managers and front-line nurses who we have been called “upstanders” in this study. To do less than this perpetuates the culture of mistreatment, as confirmed in this study and others [53]. …”
Section: Discussionsupporting
confidence: 76%
“…Bullying in the workplace runs counter to the espoused ethical values of health care organizations and must be challenged by managers and front-line nurses who we have been called “upstanders” in this study. To do less than this perpetuates the culture of mistreatment, as confirmed in this study and others [53]. …”
Section: Discussionsupporting
confidence: 76%
“…In three survey studies [19,31,38] and two qualitative studies [20,32] nurse-to-nurse hostility was reported to result in individuals feeling overwhelmed, unable to ask for help, feeling out of their depth with patient situations, fearful of making errors or causing harm, and unable to trust. The tendency to ignore requests for assistance from colleagues, especially in situations where assistance was needed to ensure patient safety or to respond to complex or demanding clinical situations was reported by respondents in four survey studies [19,31,38,42] and three qualitative studies [20,32,41].…”
Section: Resultsmentioning
confidence: 99%
“…The tendency to ignore requests for assistance from colleagues, especially in situations where assistance was needed to ensure patient safety or to respond to complex or demanding clinical situations was reported by respondents in four survey studies [19,31,38,42] and three qualitative studies [20,32,41]. …”
Section: Resultsmentioning
confidence: 99%
“…The consequences of bullying include nurses reporting poorer mental health, decreased collaboration with team members, ineffective communication, reduced work productivity, and poor job commitment. [5,12,14,1622] These consequences ultimately affected the care nurses delivered to their patients including decreased quality of care, medication errors, and patient death. [2327] Bullying among nurses previously garnered such national recognition The Joint Commission [28] issued a Sentinel Event Alert requiring all accredited hospitals to develop a code of conduct and implement processes to manage bullying.…”
Section: Introductionmentioning
confidence: 99%